Solve for x, y, z
x=-4
y=-1
z=-4
Share
Copied to clipboard
y=-5x+5z-1
Solve -5x-y+5z=1 for y.
-4\left(-5x+5z-1\right)+2z=-4 7x+5\left(-5x+5z-1\right)+5z=-53
Substitute -5x+5z-1 for y in the second and third equation.
x=-\frac{2}{5}+\frac{9}{10}z z=-\frac{8}{5}+\frac{3}{5}x
Solve these equations for x and z respectively.
z=-\frac{8}{5}+\frac{3}{5}\left(-\frac{2}{5}+\frac{9}{10}z\right)
Substitute -\frac{2}{5}+\frac{9}{10}z for x in the equation z=-\frac{8}{5}+\frac{3}{5}x.
z=-4
Solve z=-\frac{8}{5}+\frac{3}{5}\left(-\frac{2}{5}+\frac{9}{10}z\right) for z.
x=-\frac{2}{5}+\frac{9}{10}\left(-4\right)
Substitute -4 for z in the equation x=-\frac{2}{5}+\frac{9}{10}z.
x=-4
Calculate x from x=-\frac{2}{5}+\frac{9}{10}\left(-4\right).
y=-5\left(-4\right)+5\left(-4\right)-1
Substitute -4 for x and -4 for z in the equation y=-5x+5z-1.
y=-1
Calculate y from y=-5\left(-4\right)+5\left(-4\right)-1.
x=-4 y=-1 z=-4
The system is now solved.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}